IDENTIFYING THE SNP (C258T) POLYMORPHISMS OF FOXO3 GENE AND ITS ASSOCIATION WITH PRODUCTIVE PERFORMANCE OF AWASSI SHEEP - Ibadi, N. H.; Senkal , R. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was carried out to separate the DNA genetic material, determining the genotypes of the Foxo3 gene, and studying the effect of the genetic conformation of the mutation (C258T) rs 160226273, and to study the effect of genetic polymorphism of this mutation with the productive performance of Awassi sheep. A total of forty-five Awassi ewes of 2-4 years old were used currently as a source for blood sampling. These ewes produced 54 births, and their ages and weights were followed up from birth until the sixth month of age for the period from5/1 2022 to 25/6 2022.at the AL-Fayha Station for sheep Breeding. The mutation found within the studied segment (365 bp) of exon 2 of the Foxo3 gene, produced three genotypes (CC, CT, and TT), and their distribution rates were 36.36, 52.27, 11.36% respectively. The variation among these ratios was significant (p≤0.01), and the allelic frequency was 0.625 and 0.375 for both the C and T alleles. The results showed that the effect of the genotypes of the Foxo3 gene was significant (p≤0.05), on some traits represented by the ratio of solids non-fat for milk components, and some growth characteristics of lambs such as weaned weight, weight gain between birth and weaning weight, weight at six months of age, weight gain between weaning weight, weight at six months, and weights of lambs at three months of age.